Hurricane resulted in releasing more nitrogenous than carbonaceous disinfection byproduct precursors in coastal watersheds - UZUN, HABİBULLAH (ELSEVIER, 2020)
The frequency of Atlantic hurricanes has been predicted to increase significantly by the end of this century. Watershed disturbance initiated by hurricanes can alter dissolved organic matter (DOM) quantity and quality in source water dramatically. DOM is an important disinfection by-product (DBP) precursor, and thus hurricanes can have a significant impact on water treatability and drinking water safety. The interactions between land use and land cover (LULC) of a watershed and DBP formation potential (FP) in source water under hurricane events have rarely been evaluated. Here, we quantified the FPs of two carbonaceous (trihalomethanes [THMs] and haloacetic acids [HAA]) and two nitrogenous (haloacetonitrile [HAN] and N-nitrosodimethylamine [NDMA]) DBPs at eighteen sub-watersheds with varying LULC along the Yadkin-Pee Dee River basin across North and South Carolina during and after the flooding condition caused by the 2016 Hurricane Matthew. Using chlorine as a disinfectant. THM FP was 238% (+/- 117%) higher (p < .001) under the flooding condition than baseflow condition, while HAA FP did not change significantly as a result of the flooding. DOM composition under the flooding condition changed in favor of the formation of THMs rather than HAAs by a decrease of acid-like compounds and an increase in DOM aromaticity (SUVA). The FPs of studied DBPs under the flooding condition compared with the baseflow, followed the order of HAN (356.5%) > NDMA (246.4%) > THM (1152%) using chloramine as a disinfectant. Higher HAN FP and NDMA FP compared to THM IT suggested that more nitrogenous than carbonaceous DBPs precursors were released during this hurricane event. LULC analysis revealed that forested wetlands were the major contributor of THM, MA, and HAN precursors, whereas NDMA precursor was derived from developed areas. This unique study highlights the dynamic interplay between LULC and exports of carbonaceous and nitrogenous DBPs precursors during and after hurricanes. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hurricanes; Source water quality; Disinfection by-products; LULC; DISSOLVED ORGANIC-MATTER; DRINKING-WATER; FORMATION POTENTIALS; DYNAMICS; IMPACT; GENOTOXICITY; RAINWATER; CHLORINE; STORMS; RIVER